Fungistatic activity of miconazole against Candida albicans in relation to pH and concentration of nonprotonated drug - Beggs, W H (Mycoses, 1989)
At less than 10(-5) M, miconazole (MCZ) exerts a fungistatic effect on Candida albicans, presumably by interfering with ergosterol biosynthesis. The imidazole moiety of MCZ is subject to protonation (pKa approximately 6.5). Based on pKa and greater water solubility of protonated (MCZH+) versus nonprotonated (MCZo) drug, fungistatic action ought to be markedly affected by environmental pH, but apparently it is not. In this report growth phase, pH, and concentrations of MCZ and MCZo have been studied in relation to fungistasis. Yeasts were grown in a synthetic liquid medium and MCZ effects were monitored by viability determinations. Results showed that fungistatic activity is little affected by growth phase and is largely independent of drug concentration and pH. Antagonism of fungistasis by low pH was demonstrated only at less than 10(-7) M MCZ. Data supported earlier proposals that MCZo is required for biological activity and suggested that target sites are saturated at very low levels of drug.